The Relationship between Feelings-of-Knowing and Partial Knowledge for General Knowledge Questions - Norman, Elisabeth; Blakstad, Oskar; Johnsen, Øivind; Martinsen, Stig K.; Price, Mark C. (Frontiers in Psychology, 2016)
Feelings of Knowing (FoK) are introspective self-report ratings of the felt likelihood that one will be able to recognise a currently unrecallable memory target. Previous studies have shown that FoKs are influenced by retrieved fragment knowledge related to the target, which is compatible with the accessibility hypothesis that FoK is partly based on currently activated partial knowledge about the memory target. However, previous results have been inconsistent as to whether or not FoKs are influenced by the accuracy of such information. In our study (N=26) we used a recall-judge-recognise procedure where stimuli were general knowledge questions. The measure of partial knowledge was wider than those applied previously, and FoK was measured before rather than after partial knowledge. The accuracy of reported partial knowledge was positively related to subsequent recognition accuracy, and FoK only predicted recognition on trials where there was correct partial knowledge. Importantly, FoK was positively related to the amount of correct partial knowledge, but did not show a similar incremental relation with incorrect knowledge.